Application of POCCC Principles in Islamic Insurance Business Management (Takaful) in Thailand: Application of POCCC Principles in Islamic Insurance Business Management (Takaful) in Thailand - Dacharun, Montira; Tanaborworpanid, Nutpatsorn; Keawkasetkon, Phinit (RATANABUTH JOURNAL, 2025)
Takaful insurance businesses also need to develop management processes to comply with Islamic principles and build consumer confidence at the national, ASEAN and global levels. Thailand is committed to seizing the opportunities offered by the ASEAN Free Economic Zone, but lacks the management systems and strategies to enable the Islamic insurance industry to grow to its full potential. This academic article aims to present the problems and obstacles affecting the development of Islamic insurance business in Thailand, including the application of POCCC principles in the management of Islamic insurance business (Takaful) in Thailand. Thailand is committed to taking advantage of the opening of the ASEAN Free Economic Zone, particularly in expanding markets and developing competitiveness in the Islamic insurance service business (Takaful). To its full potential, this is to ensure that the Takaful insurance business in Thailand has a clear legal status and management, and is trusted by insureds, both among Thai Muslim consumers and the ASEAN Economic Community group that adheres to Islam. This will enable the economic and social system to develop steadily and preserve the interests of the people in both life and property. In addition, Thailand also needs to determine the legal status of the insurance business (Takaful). To be clear enough to define roles and responsibilities as well as criteria for business operators, the application of modern management principles is generally similar, consisting of planning, organizing, directing, coordinating and controlling. Control which can be applied to the management of insurance businesses according to Islamic principles to make management as efficient as possible. Summary of the study results: Management of insurance business according to Islamic principles (Takaful) helps Takaful insurance business in Thailand. There is an efficient, transparent and Islamic management system that is in line with Islamic principles and builds confidence among policyholders both domestically and internationally.